Wedding bell blues : a Dixie Dew mystery - Moose, Ruth (Minotaur Books, 2016)
"Beth McKenzie, owner of the Dixie Dew Bed and Breakfast, is enjoying an exciting affair with her new love, Scott. Meanwhile, the town of Littleboro, North Carolina is abuzz with gossip about Crazy Reba's upcoming nuptials. Most brides go crazy at some point, but Littleboro's resident homeless lady has had a head start: she's beloved, indulged, and most of all, eccentric. But at almost 60 or thereabouts her marriage seems a little peculiar. Sure, she's sporting a diamond big enough to choke a horse, but no one can tell if it's real, or just a Cracker Jack prize she pilfered from a yard sale. Crazy Reba's wedding plans go confirmedly awry when the bride-to-be is arrested for her fiancé's murder. Beth, determined to clear Reba's name, gets in over her head when a lady wrestler who threatened to kill her books a room at the Dixie Dew, and Robert Redford, her neighbor's white rabbit, disappears. Then Litteboro's First Annual Green Bean Festival gets up and running, a famous food writer becomes deathly ill, and Beth must battle through madcap mayhem to apprehend the culprit and save the day. Wedding Bell Blues is Ruth Moose's sequel to her winning debut, featuring her colorful array of characters and more laughs and hilarity"--